An Evaluation of the Industrial Research Assistance Program - John Lester (The School of Public Policy Publications)
The Industrial Research Assistance Program (IRAP) supports R&D performed by small and medium-sized enterprises (SMEs), financially assists not-for-profit organizations that provide innovation services to SMEs and participates in the Youth Employment and Skills Strategy. IRAP funding is approximately $400 million for the 2024–25 fiscal year. About 90 per cent of the funding supports R&D performed by SMEs, which is the focus of this paper.